The Composition and Cellular Sources of CSPGs in the Glial Scar After Spinal Cord Injury in the Lamprey - Zhang, Guixin; Jin, Li-Qing; Rodemer, William; Hu, Jianli; Root, Zachary D.; Medeiros, Daniel M.; Selzer, Michael E. (Frontiers in Molecular Neuroscience, 2022)
Axon regrowth after spinal cord injury (SCI) is inhibited by several types of inhibitory extracellular molecules in the central nervous system (CNS), including chondroitin sulfate proteoglycans (CSPGs). CSPGs also are known to be components of perineuronal nets (PNNs). The axons of lamprey regenerate following SCI, even though the lamprey spinal cord contains CSPGs, and their neurons are enwrapped by PNNs. Previously, we showed that by 2 weeks after spinal cord transection in the lamprey, expression of CSPGs increased in the lesion site, and thereafter, decreased to pre-injury levels by 10 weeks. Enzymatic digestion of CSPGs in the lesion site with chondroitinase ABC (ChABC) enhanced axonal regeneration after SCI and reduced retrograde neuronal death. Lecticans (aggrecan, versican, neurocan, and brevican) are the major CSPG family in the CNS. Previously, we cloned a cDNA fragment that lies in the most conserved link-domain of the lamprey lecticans and found that lectican mRNAs are expressed widely in lamprey glia and neurons. Because of the lack of one-to-one orthology with jawed the vertebrate lecticans, the four lamprey lecticans were named simply A, B, C, and D (Root et al., 2021). Using probes that distinguish these four lecticans, we now show that they all are expressed in glia and neurons, but at different levels. Expression levels are relatively high in embryonic and early larval stages, gradually decrease, and are upregulated again in adults. Reductions of Lecticans B and D are greater than those of A and C. Levels of Lectican B and D mRNAs increased dramatically after SCI. Lectican D continued to be upregulated for at least 10 weeks. Multiple cells, including glia, neurons, and microglia/macrophages, expressed lectican mRNAs in the peripheral zone and lesion center after SCI. Thus, as in mammals, lamprey lecticans may be involved in axon guidance and neuroplasticity early in development. Moreover, neurons, glia and microglia/macrophages, are responsible for the increase in CSPGs during the formation of the glial scar after SCI.